Sensory Evaluation of Complementary Foods Developed Using Malted Grains Flour to Overcome Malnutrition - , Sukhmandeep Kaur; , Navjot Kaur (Archives of Current Research International, 2025)
The growing population and their increasing demands for sustainable foods especially economic and nutritionally rich still needs to be fulfilled to overcome malnutrition in some under-developed and developing countries. Malnutrition is a major public health issue affecting mainly young children due to higher demands for nutritious and healthy foods. Therefore, this study was carried out with the objective to develop various complementary foods such as Dalia, Khichdi, Panjiri, Pancakes and Seviyan by using combination of easily available staple malted grains such as wheat, mung and ragi, along with carrot and flaxseed powder to provide nutrient density to children’s diet that may be helpful to combat malnutrition. The foods were developed using different ratios of flours and evaluated for sensory properties to ascertain the acceptability of the foods. The results of the study revealed the overall acceptability scores for treatment samples such as Dalia, Khichdi, Panjiri, Pancakes and Seviyan were 7.55, 8.02, 7.74, 7.86 and 7.64, respectively. Therefore, the combination of these flours can be utilized for the development of various complementary foods in order to overcome the problem of malnutrition among young children.